Green Strategies During Lower of Occupancy: The Best Practices of Facilities Management for Energy Optimization in Commercial Office Buildings - Mirza Faizal, Muhammad Adli; Agus Salim, Nuzaihan Aras (Journal of Advanced Research Design, 2024)
The increasing global emphasis on sustainability and environmental responsibility has influenced the field of Facilities Management (FM). Emphasis on energy consumption during peak hours has been widely studied by many researchers. However, FM also plays an important role in optimizing the use of energy during lower occupancy periods energy. This paper explores the implementation of green strategies within FM practices to increase and optimize energy use during lower of occupancy during working hours. This paper investigates the current green strategies for energy efficiency in commercial office buildings that can be conducted during lower of occupancy. Interviews and observation are conducted for three selected buildings to collect data and analyze which practices are suitable. This research uses qualitative methods by interviewing facility managers and BO Chargeman to gather detailed information and observations to gain more understanding of the situation of research by assembling the current practices of green strategies. This result will help the data collection to be more effective in gathering varied recommendations of the best practices of green strategies on energy efficiency focusing on lower occupancy periods. At the end of this study, it will figure out the best practices of green strategies that can be implemented in building energy efficiency purposes focusing lower occupancy periods. The finding shows adaptation to technology and training to provide awareness for occupants is the best practice to empower towards facility manager in Malaysia for energy optimization approaches.